What are the effects of strength training and aerobic exercise training for muscle disease? - A Cochrane Review summary with commentary - Ayesha Afridi; Farooq Azam Rathore (Medical Journals Sweden, 2021)
The aim of this commentary is to discuss from a rehabilitation perspective the published Cochrane Review (1) by Voet NBM et al., under the direct supervision of Cochrane Neuromuscular Group. This Cochrane Corner is produced in agreement with the Journal of Rehabilitation Medicine by Cochrane Rehabilitation.